Desarrollo psicomotor y su relación con la alimentación en los niños de los CNH de Chantaco y Chiquiribamba del MIES-Loja, año 2014 - Apolo González, Mariuxi Janeth (2015)
The present research has been focused in practices of infant feeding, toddler, and it´s influence in the psychomotor development in the CNH (acronym in spanish) of Chuquiribamba y Chantaco of MIES-LOJA, year 2014, research of transversal correlational kind, done to children aged from 0 to 3 that attended CNH, where surveyed feeding practices and was evaluated the psychomotor development using the Denver´s Test. Given as a result that the early beginning of breastfeeding help to improve the psychomotor development of the breastfed presenting less abnormal proofs than the ones that didn’t receive an early breastfeeding (12% vs 42%), therefore the ones that didn’t receive an exclusive breastfeeding showed a bigger percentage of abnormal proofs compared to the ones that did receive (53.5% vs 21%), the ones that receive a continuous breastfeeding at age one showed a bigger percentage of normal proofs compared to the ones that didn’t (70% vs 51%). In infant breastfed that received a minimum frequency of meals showed less abnormal proofs, that the ones that didn’t receive (19% vs 25%), Nevertheless not having a broad population, the results obtained in this research, shows that the breastfeeding helps to improve a better psychomotor development as well as feeding practices KEYWORDS: BREASTFEEDING, PSYCHOMOTOR DEVELOPMENT, DENVER`S TEST.